2010
DOI: 10.1007/s12274-010-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-controlled fabrication of sulfonated graphene/polyaniline nanocomposites by liquid/liquid interfacial polymerization and investigation of their electrochemical properties

Abstract: A novel morphology-controlled strategy has been developed to fabricate sulfonated graphene/polyaniline (SGEP) nanocomposites by liquid/liquid interfacial polymerization. Sulfonated graphene (SGE) sheets were synthesized and used as both a macromolecular acid dopant and substrate for the polymerization of polyaniline (PANI), affording the SGEP nanocomposites. The morphology of PANI in the nanocomposites can be controlled to be either nanorods or nanogranules by varying the synthesis conditions. The morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(55 citation statements)
references
References 36 publications
2
52
1
Order By: Relevance
“…95 The composite exhibited a specific capacitance of 763 F g À1 with capacity retention of 96% after a 100-cycle charging/discharging test and good rate performance. Surfactant (tetrabutylammonium hydroxide and sodium dodecyl benzenesulfonate)-stabilized graphene (SSG) is also used in the preparation of graphene/PANI NF composites.…”
Section: Graphene/pani Compositesmentioning
confidence: 98%
“…95 The composite exhibited a specific capacitance of 763 F g À1 with capacity retention of 96% after a 100-cycle charging/discharging test and good rate performance. Surfactant (tetrabutylammonium hydroxide and sodium dodecyl benzenesulfonate)-stabilized graphene (SSG) is also used in the preparation of graphene/PANI NF composites.…”
Section: Graphene/pani Compositesmentioning
confidence: 98%
“…Beside the role as supports, the functional graphene also acted as the doping agent for the conductive polymers [12,14,22,23]. It was also found that the morphology of the prepared composites was influenced dramatically by the different mass ratios of the functional graphene [11,14,16,22,38].…”
Section: Introductionmentioning
confidence: 96%
“…It was also found that the morphology of the prepared composites was influenced dramatically by the different mass ratios of the functional graphene [11,14,16,22,38]. The effect of dopant on morphology formation in graphene/conductive polymer nanocomposites was also investigated with graphite nanoplatelet as support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene and its derivatives have also attracted considerable attention in recent years because of their unique physical properties [22][23][24].…”
Section: Introductionmentioning
confidence: 99%